Cellular physiology of the turtle visual cortex: synaptic properties and intrinsic circuitry - Kriegstein, AR (J Neurosci, 1986)
We have examined the synaptic physiology of the isolated dorsal cortex of the turtle, Pseudemys scripta elegans. Electrical stimulation of afferent pathways elicited distinct, stereotyped responses in pyramidal and stellate neurons. Single shocks evoked a long-lasting barrage of excitatory postsynaptic potentials (EPSPs) in stellate cells, and led to a burst of several action potentials. Under the same circumstances, pyramidal cells displayed a small amount of short-latency excitation, but this was accompanied by a profound and prolonged set of inhibitory post-synaptic potentials (IPSPs). Synaptic excitation of the distal dendrites of pyramidal cells could evoke dendritic action potentials that were visible at the soma as small all-or-none spikes rising from the hyperpolarized level of the IPSP. There appeared to be two mechanistically different types of IPSPs in pyramidal cells. The first occurred at short latency, could produce a very large conductance increase, reversed polarity at -71 mV, and was chloride-dependent. The second was generally smaller and more protracted, had a relatively negative reversal potential of -85 to -95 mV, and was insensitive to chloride injection. Focal application of small doses of the putative inhibitory neurotransmitter gamma-aminobutyric acid (GABA) onto the somata of pyramidal cells caused a conductance increase and hyperpolarization. This response had features in common with the short- latency IPSP, including an identical reversal potential. Application of large doses of GABA to the somata of pyramidal cells or smaller doses to their dendrites elicited multiphasic or purely depolarizing responses that were at least partly due to time- or space-dependent shifts of the equilibrium potential of the response. Bicuculline methiodide, a potent GABA antagonist, depressed both the responses to GABA and the short-latency IPSP, but not the long-latency IPSP; synchronized epileptiform burst discharges also resulted. These findings, together with responses to locally applied electric shocks and the excitatory amino acid glutamate, suggested that inhibition of pyramidal cells was generated intrinsically by stellate cells, and that the cortical circuit provides pathways for both feedforward and feedback GABAergic inhibition. The data also suggest that pyramidal cells are mutually excitatory. These features are similar to the basic intrinsic circuitry in the telencephalic cortices of mammals.